The challenge of recruiting and engaging reluctant non-expert representatives. (February 2021) - Giorgi, Alberta
Methodological literature dealing with the challenges in sampling, recruiting and engaging research participants for qualitative interviews usually assumes that potential informants are informed. But what happens when the potential informants make it clear that they have little to say because under-informed on the topic? This article explores the challenges in recruiting and engaging under-informed research participants by revisiting my fieldwork experience as a researcher for the ERC-funded project GRASSROOTSMOBILISE – Directions in Religious Pluralism in Europe. The article describes potential interviewees' claims of under-information as a specific type of reluctance, displaying in both the recruitment and the interview processes, and discusses the potential strategies to overcome this reluctance by paying attention to the role of researchers.